High breast milk IL‐1β level is associated with reduced risk of childhood eczema. Issue 10 (28th June 2016) - Jepsen, A. A.; Chawes, B. L.; Carson, C. G.; Schoos, A.‐M. M.; Thysen, A. H.; Waage, J.; Brix, S.; Bisgaard, H.
Summary: Background: We recently demonstrated a dual effect of breastfeeding with increased risk of eczema and decreased risk of wheezing in early childhood by increasing breastfeeding length. We hypothesize that immune mediators in breast milk could explain such association either through a direct effect or as a surrogate marker of maternal immune constitution. Objective: To investigate the possible association between cytokine and chemokine levels in breast milk and development of eczema and recurrent wheeze during early childhood. Methods: Levels of 19 pro‐inflammatory and immunoregulatory cytokines and chemokines were measured in 223 breast milk samples from mothers in the Copenhagen Prospective Study on Asthma in Childhood2000 (COPSAC) high‐risk birth cohort. Eczema and recurrent wheeze at the age of 0–3 years were prospectively diagnosed by COPSAC physicians adherent to predefined validated algorithms. Association analyses were performed by Cox regression adjusting for potential confounding factors and by multivariable principal component analysis. Results: Increased IL‐1β in breast milk (≥ 0.7 pg/mL) was associated with more than a halved risk of eczema before age three (aHR = 0.41; 95% CI = 0.24–0.68; P < 0.001), which remained significant after false discovery rate adjustment ( P = 0.008). The principal component analysis confirmed that a mediator pattern dominated by high levels of IL‐1β, IL‐17A, and CCL17 and low levels of CXCL1 and TSLP in breast milk protected against eczema (aHR = 0.82; 95% CI = 0.68–0.98; P = 0.03). No associations were observed for recurrent wheeze. Conclusions and Clinical Relevance: Elevated breast milk IL‐1β level was associated with decreased risk of early childhood eczema suggesting either a direct protective effect of IL‐1β or IL‐1b acting as a proxy for a healthy maternal immune system protecting high‐risk offspring from eczema.